Large stiffness thermoformed open cell foams with auxeticity. (September 2020) - Zhang, Qicheng; Lu, Wenjiang; Scarpa, Fabrizio; Barton, David; Lakes, Roderic S.; Zhu, Yunpeng; Lang, Ziqiang; Peng, Hua-Xin
Highlights: Open cell foams with auxeticity and modulus 5 times larger than the stiffest auxetic polymeric open cell foam. The loss factors exhibited by these thermoformed foams range between 2% and 6%. The foam shows some evident size effects with thinner specimens possessing lower stiffness and larger auxeticity. The data provided in this work are also instrumental for designs where stiffness, auxeticity and energy absorption are essential characteristics. Abstract: Open cell foams with auxeticity and modulus 5 times larger than the stiffest auxetic polymeric open cell foam featured in scientific literature are developed in this paper by using vacuum bags and autoclave following a thermoforming process. The resulting foam is transverse isotropic with microstructures exhibiting elongated semi-reticulated configurations, and contains a plane in which the auxetic behavior is evident. Tensile and compression quasi-static tests were carried out on samples cut along different directions and with different thicknesses. Foams have been also subjected to tensile training at different maximum strains to assess their mechanical performance. The tensile modulus and Poisson's ratio values of the auxetic foams produced in this work can reach 25 MPa and -0.4 in one plane and can feature a negative Poisson's ratio up to -1.3 for thinner specimens. Smaller thicknesses and higher tensile training strains can also reduce the stiffness but enhance the auxeticity of this porous material. Graphical abstract: Image, graphical abstract